Psuedo Demokrasi dalam Ranah Koalisi Partai Politik di Indonesia - Sidi Alkahfi Setiawan (JURNAL RECHTENS, 2016)
This paper uses normative juridical research method to gather a wide range of legislation as the legal basis for the establishment of political parties and compare it with the present context where the presidential system of government in Indonesia, which uses multi-party system resulted not dimunculkannya the majority party in parliament and thus require coalition between parties political. Uniquely in the practice of constitutional Coalition political party applied only to a parliamentary system instead of presidential such as in Indonesia. This phenomenon resulted in the coalition of political parties in Indonesia is not ideological but simply Coalition Coalition of interests that are very loose. This loose coalition that very often resulted in the migration of the room from each party from opposition into joining the government or vice versa depending on the extent to which the interests of the party to be accommodated. It is then called pseudeo democracy by political parties in the coalition government mechanism. Because the coalition is only based on the interest result in the emergence of changes of political party support in both the legislative and executive institutions specifically by smaller parties voiced both in parliament and in the executive.